THE STUDENTS’ PERCEPTION TOWARDS READING STRATEGIES AT 2ND SEMESTER STUDENTS OF STBA JIA IN ACADEMIC YEAR 2021/2022 - Esterria Romauli Panjaitan; Fitra Mandela; Ade Surista (PROJECT (Professional Journal of English Education), 2024)
This study discussed STBA JIA students’ perception of reading learning in the 2nd semester of  academic year 2021/2022 of STBA JIA, Bekasi”. The purpose of this study is to investigate  students' perceptions of reading strategies and to demonstrate that reading strategies can help  students  continue  their  learning  to  the  next  level.  This  research  is  carried  out  utilizing  a  qualitative research method, namely a descriptive design. The total number of students was 51  students of 2nd semester, and the data was collected through interviews questionnaires. The data  analysis technique used was to explain the data from the questionnaire, which was handled  using Google Forms. Google Form serves as a digital form to gather data in this study, and the  findings serve to analyze the data. To put it another way, it was transformed into a pie or bar  chart. The findings revealed that, in general, students' perceptions of reading strategies were  favorable (positive), since most of them still pay attention and perform pre-reading, during  reading,  and  after  reading  strategies.  Reading  strategies  will  always  help  and  support  the  students in their reading comprehension performance.